2014
DOI: 10.1097/ta.0000000000000086
|View full text |Cite
|
Sign up to set email alerts
|

Flail chest injuries

Abstract: Epidemiologic/prognostic study, level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
113
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 293 publications
(120 citation statements)
references
References 20 publications
3
113
0
4
Order By: Relevance
“…Blunt chest trauma such as rib fractures, lung contusion, pneumothorax, and hemothorax have been frequently associated with extrathoracic injuries on the head, the abdomen, and the extremities 1, 8, 14, 15, 18, 19, 20. Of these injuries, it is reported that the four variables, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Blunt chest trauma such as rib fractures, lung contusion, pneumothorax, and hemothorax have been frequently associated with extrathoracic injuries on the head, the abdomen, and the extremities 1, 8, 14, 15, 18, 19, 20. Of these injuries, it is reported that the four variables, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Of these injuries, it is reported that the four variables, i.e. flail chest, lung contusion, the number of rib fractures, and severe head injury, may cause PMV 8, 14…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations